The forgotten smoker: a qualitative study of attitudes towards smoking, quitting, and tobacco control policies among continuing smokers - Uppal, Navneet; Shahab, Lion; Britton, John; Ratschen, Elena (BioMed Central, 2013)
Background: Although research suggests that the majority of smokers want to quit smoking, the uptake of Stop Smoking Services, designed to assist smokers with quitting, remains low. Little is known about continuing smokers who do not access these services, and opportunities to influence their motivation and encourage quit attempts through the uptake of services. Using PRIME theory, this study explored differences between continuing smokers who had varying levels of motivation to quit, in terms of their plans to quit, evaluative beliefs about smoking, cigarette dependence, and attitudes towards tobacco control policies and services. Methods: Twenty-two current smokers, recruited from the community, were classified by motivation level to quit using a self-report questionnaire (two groups: high/low). Four focus groups (n=13) and individual interviews (n=9) were conducted with both groups using an interview guide incorporating aspects of PRIME theory. Discussion areas included motives for smoking, attitudes towards smoking and quitting, perceptions of dependence, motives for quitting, barriers to quitting, and attitudes towards existing and impending tobacco control policies and services. Verbatim transcripts were analysed using thematic framework analysis. Results: All participants expressed low motivation to quit during discussions, despite some initially self-classifying as having high explicit levels of motivation to quit. Both groups reported similar attitudes towards smoking and quitting, including a perceived psychological addiction to smoking, positive evaluations about smoking which inhibited plans to quit, and similar suggested methods to increase motivation (simply wanting to, save money, improve health). Most felt that they ‘ought’ to quit as opposed to ‘wanted’ to. Little influence was ascribed towards tobacco control policies such as plain packaging and hidden sales displays, and participants felt that price increases of tobacco products needed to be considerable in order to influence motivation. Highly motivated smokers expressed more willingness to visit Stop Smoking Services, although none had done so. Conclusion: Continuing smokers’ attitudes towards smoking and quitting suggests that research and policy need to focus on increasing smokers’ implicit motivation to quit smoking, even for those who classified themselves as having high motivation to quit. Targeted information and further education about Stop Smoking Services is required to increase uptake.